PENGGEMUKAN KEPITING BAKAU (Scylla serrata) SISTEM APARTEMEN SEBAGAI ATRAKSI WISATA DI PANTAI TAKARI BANGKA BELITUNG - Adibrata, Sudirman; Wahidin, La Ode; Guskarnali, Guskarnali (Universitas Mataram, 2024)
The significant tourism potential at Takari Beach must be managed well to attract tourists, including providing the crab apartment tourist attraction. Crab fattening activities using an apartment system at tourist locations can develop the mud crab (Scylla serrata) species. This is expected to increase visitor interest in educational tourism from the Takari Beach tourist destination. PKM activities aim to develop tourist attractions through the apartment system of fattening mangrove crabs (Scylla serrata) by KTH HKM Takari Bangka Belitung. This activity was carried out from May to November 2023 at Takari Beach, Rebo Village, Sungailiat District, Bangka Regency, Bangka Belitung. The method is carried out in a participatory manner that prioritizes the role and participation of the HKM Takari Manager as a supporter in the apartment system of mangrove crab fattening. The results show that the KTH HKM Takari Manager was given a business permit for forest utilization covering 59 Ha. Adding a tourist attraction in the form of mangrove crab (Scylla serrata) apartments on Takari Beach is an innovation the management can develop. Land preparation and construction of crab apartments was carried out over 3 months with 54 apartment boxes. The procurement of young mud crabs is managed by HKM Takari Management and purchased from fishermen who catch mud crabs, which are then fattened in the crab apartment. Measuring the length and weight of mud crabs, water quality, and substrate is very helpful in analyzing the growth and survival of mangrove crabs sustainably. Innovation in tourist attractions with apartment systems fattening mangrove crabs gives new enthusiasm to managers. The mangrove crab apartment tourist attraction is expected to support sustainable tourism management.